Agricultural policy processes and the youth in Malawi - Mapila, Mariam A. T. J. (International Food Policy Research Institute, 2014)
Evidence exists which shows growing disillusionment with and disinterest in agricultural-based livelihoods among the youth in Africa south of the Sahara. This disillusionment raises concerns for the future of agriculture for the developing world as it can lead to higher rural urban migration, unemployment and lowered agricultural productivity. The engagement of youth in agricultural policy formulation processes is seen as one avenue for motivating youth engagement in agriculture. This research seeks to develop a contextual understanding of the level of engagement of youth in agriculture thus providing evidence which can be used to stimulate youth involvement in the sector. Using a mixed-methods approach, this study analyzes the determinants of the engagement by southern African youth in agricultural policy processes using Malawi as a case study.